Understanding Air-Passengersâ€™ Volitional Behavior Toward Compliance with Aviation Health and Safety Guidelines : Evidence from Indian Domestic Passengers - Jaiswal, Kamal; Singh, Balgopal (Indian Journal of Marketing, 2023)
Purpose : This study aimed to understand the air passengersâ€™ rationality and morality associated with the volitional compliance behavior of health and safety guidelines for a healthy and safe air travel experience. Methodology : The design of the research framework was based on integrating the theory of planned behavior and norm activation theory. Four hundred seventeen domestic air passengers participated in the study through an online questionnaire distributed through social media. Path analysis was carried out using covariance-based structural equation modeling for hypotheses testing. Findings : The study established that attitude toward behavior, perceived behavioral control, and personal norms significantly affected air passengersâ€™ volitional compliance behavior. It was also confirmed that â€œpersonal normsâ€ partially mediated the effect of â€œattitude towards compliance behaviorâ€ and â€œperceived behavioral control.â€ Practical Implications : This study provided adequate evidence to understand the components that influence the volitional behavior of passengers toward compliance with health and safety guidelines. Originality : The study provided novel insights into integrating behavioral theories associated with rationality and morality into understanding volitional behavior.